Americas Start-Ups – Inspiration for a Copycat in Europe? : - Klijer, Sven (2022)
This thesis recognizes the opportunity that stems from start-ups in America and a potential launch of copycat companies in Europe. It describes important factors for start-ups and copycats. Based on the industries of the fastest-growing companies in America, certain industries are picked for further exploration. Two ideas from the “E-Commerce” and “Sales & Marketing” industry are thoroughly analyzed. The analysis aims to answer the feasibility of a potential launch of a copycat model in the European market. Based on extensive market research and interviews with investors in Europe a final assessment is developed. Both companies would face different severe challenges that make a market launch in Europe unfeasible. Therefore, the investigated business ideas from the US market cannot serve as an inspiration for founders in Europe.